2016
DOI: 10.1080/07391102.2016.1155171
|View full text |Cite
|
Sign up to set email alerts
|

A new mechanism of post-transfer editing by aminoacyl-tRNA synthetases: catalysis of hydrolytic reaction by bacterial-type prolyl-tRNA synthetase

Abstract: Aminoacyl tRNA synthetases are enzymes that specifically attach amino acids to cognate tRNAs for use in the ribosomal stage of translation. For many aminoacyl tRNA synthetases, the required level of amino acid specificity is achieved either by specific hydrolysis of misactivated aminoacyl-adenylate intermediate (pre-transfer editing) or by hydrolysis of the mischarged aminoacyl-tRNA (post-transfer editing). To investigate the mechanism of post-transfer editing of alanine by prolyl-tRNA synthetase from the path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
2
6
0
Order By: Relevance
“…However, the most accurate and illustrative estimation of the model is [an] implementation of the newborn topology in the MD simulation. , which confirm[s] a better compliance of RESP model with experimental data, described in the paper [10]. It is evident that a decrease of electrostatic interaction energy value during the MD is caused by an incorrect turn of alanine radical and loss of its hydrogen bonds and disappearance of water molecules (sterical repulsion), which are responsible for nucleophilic attack and hydrolysis.…”
Section: Parameterizing a Novel Residuesupporting
confidence: 82%
See 4 more Smart Citations
“…However, the most accurate and illustrative estimation of the model is [an] implementation of the newborn topology in the MD simulation. , which confirm[s] a better compliance of RESP model with experimental data, described in the paper [10]. It is evident that a decrease of electrostatic interaction energy value during the MD is caused by an incorrect turn of alanine radical and loss of its hydrogen bonds and disappearance of water molecules (sterical repulsion), which are responsible for nucleophilic attack and hydrolysis.…”
Section: Parameterizing a Novel Residuesupporting
confidence: 82%
“…From the Figure it becomes evident that RESP charge gives much more accurate and reliable results, which correlate with the experimental data [10]. The molecular dynamics of ProRS system also aimed at investigation of the 2'OH group impact and showed the conformity between biochemical study and computational calculations (not shown here).…”
Section: Application Of the Methods In A Fundamental Studysupporting
confidence: 69%
See 3 more Smart Citations